A comparison of inflammatory mediator expression between palmoplantar pustulosis and pompholyx. (26th June 2013) - Kim, D.Y.; Kim, J.Y.; Kim, T.G.; Kwon, J.E.; Sohn, H.; Park, J.; Lim, B.J.; Oh, S.H.
Abstract Background Both palmoplantar pustulosis (PPP) and pompholyx are clinically characterized by acute eruptions of vesicles or pustules on the palms or soles. Objectives This study aims to compare the expression of certain inflammatory mediator genes and proteins between patients with PPP and pompholyx using skin tissue samples. Methods Skin biopsies obtained from lesional skin from patients with PPP (n = 7) and pompholyx (n = 5) were analysed by quantitative RT‐PCR to measure the mRNA levels of nine genes, including IL‐4, IL‐8, IL‐9, IL‐17, IL‐22, IFN‐γ, CCL‐20, granzyme and perforin. For immunohistochemical analysis, 34 paraffin‐embedded skin specimens (PPP, n = 22; pompholyx, n = 12) were stained with anti‐IL‐8, IL‐17A, IL‐22 and granzyme B antibodies. Results Of genes analysed, IL‐8 and IL‐17A mRNA expression levels were significantly higher in the PPP group than the pompholyx group (P = 0.012 in both), whereas the mRNA expression of granzyme B was significantly higher in pompholyx when compared with PPP (P = 0.004). Regarding the IL‐17A immunohistochemical staining, tissue from the PPP lesions contained significantly more IL‐17A+ cells in both the epidermis and papillary dermis when compared with pompholyx (P < 0.001 and P = 0.019 respectively). Moreover, the intensity of the IL‐8 immunoreactivity was also greater in the PPP skin lesions than the pompholyx tissue (P < 0.001). Conclusions IL‐8 and IL‐17A, both are increased in PPP tissue, may represent important immunologic mediators that help to differentiate this clinical entity from pompholyx. This study may provide useful clues in distinguishing PPP from pompholyx, as well as helping to understand the pathogeneses of these two diseases.